A 'revolver' evolving: the careers of a Boulton & Watt rotative steam engine at the Whitbread Brewery, London and the Powerhouse Museum, Sydney, 1784–2020. (15th July 2020) - Miller, David Philip; Rudder, Debbie
Abstract : Examines the origins, and working life of the oldest surviving rotative steam engine, the Boulton & Watt engine installed in Whitbread's brewery, London, in 1785, and its museum career in Sydney, Australia